2013
DOI: 10.3945/ajcn.112.054445
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and breast cancer in Saudi Arabian women: case-control study

Abstract: An inverse association exists between serum 25(OH)D concentrations and breast cancer risk in Saudi Arabian women. This trial was registered at clinicaltrials.gov as NCT01817231.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 43 publications
2
24
0
1
Order By: Relevance
“…With a mean of 17.8 ng/mL of serum vitamin D in the breast cancer patients as compared to the mean of 25.9 ng/ mL in healthy controls, the present study shows agreement with previous studies in Saudi Arabia [11] and in other parts of the world. [2,3,4] The present study also shows that levels of vitamin D in triple negative breast cancer with mean of 13.3ng/mL is lowest among all the subtypes.…”
Section: Discussionsupporting
confidence: 92%
“…With a mean of 17.8 ng/mL of serum vitamin D in the breast cancer patients as compared to the mean of 25.9 ng/ mL in healthy controls, the present study shows agreement with previous studies in Saudi Arabia [11] and in other parts of the world. [2,3,4] The present study also shows that levels of vitamin D in triple negative breast cancer with mean of 13.3ng/mL is lowest among all the subtypes.…”
Section: Discussionsupporting
confidence: 92%
“…A protective effect of vitamin D against breast cancer has been suggested in several studies [1e3], which has been related to sunlight [4], dietary intake [5], vitamin D supplement [6e8], and ethnic background [9,10]. Studies regarding the association between serum 25-hydroxyvitamin D (25OHD) and breast cancer risk [11,12] have, however, not been conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that vitamin D 3 regulate the level of phosphorus and calcium in the blood by participating in the process of mineral metabolism and bone growth and this was confirmed by the results in (Table 1-3). In the absence of vitamin D 3 , calcium and phosphorus does not absorbed with high efficiency (Calvo and Uribarri, 2013;Yousef et al, 2013) and thus withdrawn from the bones into the blood and this may not seen clearly in the blood and this is what shown in the (Table 1-4) and as a result increase the level of the enzyme alkaline phosphatase which is one of the most important clinical biochemical indicators of osteoporosis (Gonzlez-Perez et al, 2011). This study showed that osteoporosis may increases the incidence of uterine cancer.…”
Section: Discussionmentioning
confidence: 79%